Investigation of numerical and experimental assessment of melting behavior of phase change material in U tube heat exchanger - Erdogan, Abdulhamit; Cakmak, Gulsah (Elsevier, 2023)
This study analyzes the melting process and temperature changes of a phase change material (PCM) in a U-tube heat exchanger, both experimentally and numerically. In the study, PCM was placed in a U-tube heat exchanger body and hot water was sent to the heat exchanger with a flow rate of 1.75 l/min and a temperature of 60 degrees C. In the study, the equations valid for continuity, momentum and energy were solved numerically by considering the phase change effects. The melting process was simulated and the melting percentages of the PCM at different time intervals were calculated to show the transition zones from the solid phase to the liquid phase. The PCM was initially subjected to hot water at 333 K at 300 K. In the experimental study, the PCM temperature reaches 306 K between the first 700-1200 min and melting is observed. This tem-perature is 303 K for numerical operation. After 3800 min, the PCM was observed to have completely melted for experimental and numerical study. The hardest and slowest melting part of the PCM is the area farthest from the center of the heat exchanger. In the comparison, approxi-mately 4% error rate was determined between the measured and calculated values.
Keywords: Finite volume method; Phase change material; U-tube heat exchanger